Mangrove vegetation and fish diversity in Kaledupa Island, Wakatobi National Park, Southeast Sulawesi, Indonesia - Yuni Tri Hewindati; Ernik Yuliana; Hasan Eldin Adimu; Wibowo A. Djatmiko (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Hewindati YT, Yuliana E, Winata A, Adimu HE, Djatmiko WA. 2023. Mangrove vegetation and fish diversity in Kaledupa Island, Wakatobi National Park, Southeast Sulawesi, Indonesia. Biodiversitas 24: 1766-1772. The purpose of the study is to analyze the association of mangrove ecosystems with fish diversity at Kaledupa Island, Wakatobi National Park (WNP), Southeast Sulawesi, Indonesia. The study was conducted around the mangrove areas of Balasuna and Tampara villages. Observations and measurements of mangrove vegetation were collected using quadrats of 10×10 m2. In addition, fish data were collected on the fish catches of fishermen who used a sero (a set net). The mangrove data was analyzed using the Importance Value Index (IVI), whereas the fish diversity was analyzed descriptively and length-weight correlation. The results indicated that the Tampara mangrove was dominated by Bruguiera gymnorrhiza with an IV of 172.31, followed by akkapanda (Rhizophora apiculata) and ongke (R. mucronata) with an IVI of 68.15 and 59.54, respectively. The Balasuna mangrove was dominated by R. apiculata, followed by B. gymnorrhiza and R. mucronata, with IVI of 143.67, 93.25, and 45.84, respectively. A total of 74 fish species were found at the two sites, including 63 species of reef fish and 11 species of non-reef fish. Based on the analysis of the length-weight correlation, it was found that the fish captured around the mangrove were not well-fed. From this result, it is presumed that food availability in the study location is reducing due to anthropogenic activities like tourism and transportation. Hence, it is proposed that periodic monitoring should be carried out to enhance the ecological health of the mangroves to ensure the fishery production services of mangroves.